The effect of training interruption on some physiological variables of Iraqi Premier League volleyball players - Al-Safi, Prof. Dr. Asaad Adnan Aziz; Al-Khafaji, Prof. Dr. Ahmed Abdul Zahra; Al-Jubouri, L.Dr. Ali Jawad Kadhim (Sulaimani Journal for Humanities, 2026)
The interruption of training during the transitional period is a very important topic that worries both coaches and players. This is due to the loss of physiological adaptation in the athlete's internal organs during this break, compared to the period of training and competition. This necessitates thorough investigation and study across various disciplines, examining the duration of the interruption and its impact on the overall physiological changes occurring in the athlete's body. This will provide coaches with a clear picture of how to facilitate the athlete's return to the appropriate level of adaptation in a shorter time and with high efficiency. It is well-known that regular physical training leads to physiological adaptation in many of the body's systems. Conversely, interruption of training leads to the loss of the resulting physiological adaptation. An interruption of training refers to a temporary break from regular physical training aimed at developing or maintaining physical fitness components, which often occurs after the end of the sports season and before the start of the new season. Scientific studies conducted on non-athletes, endurance athletes, and power athletes have all indicated that optimum oxygen consumption decreases by 6-20% after a four- to eight-week break from physical training, and that this decrease worsens with longer periods of inactivity. Studies also confirm that the physiological adaptations resulting from several months of physical training can diminish after a one- to four-week break. This highlights the importance of research into the impact of training breaks on adaptation and anaerobic processes, specifically on the levels of certain physiological variables in Iraqi Premier Volleyball League players. The researchers employed a descriptive survey methodology, as it best suited the nature of the research problem. The research sample consisted of the players of the Middle Euphrates Premier League volleyball clubs for the 2023-2024 season, representing four clubs: Al-Daghara, Al-Qasim, Al-Kufa, and Al-Rawdatain. A total of 58 players were initially selected, and 36 were chosen randomly by lottery. These 36 players constituted the research sample, representing 62.0689% of the original research population. The most important conclusions and recommendations are: The third training break, occurring eight weeks after the end of the training season (56 days), significantly reduced the physiological variables of the volleyball players. This break also decreased the players' performance, consequently lowering the levels of physiological variables such as blood cell volume, red blood cell count, and percentage. Hematocrit, blood lactate concentration, heart rate, stroke volume, cardiac output, ejection fraction (EF%), systolic blood volume (CL). The recommendations are: to focus attention on training with appropriate and correct methods during the end of the sports season and after the training break period to maintain the efficiency level of volleyball players and thus maintain the level of physiological variables. Relying on the results, data, and models of training break periods as an important and essential part at the end of each sports season to identify the most important obstacles that negatively affect players and thus maintain their performance level.
Keywords: Discontinuation of training; physiological changes; volleyball